Efisiensi Program Aplikasi Opera Terhadap Produktivitas Departemen Front Office di Montigo Resort Nongsa - Alexander Dwi Setyono Putro; Titik Akiriningsih; Kris Cahyani Ermawati (Sekolah Tinggi Pariwisata Sahid Surakarta, 2020)
This study aims to: (a) describe the efficiency of the OPERA application program at Montigo Resort Nongsa, and (b) the effect of the OPERA application program on the productivity of the Front Office department at Montigo Resort Nongsa. Researchers used qualitative research methods, by obtaining data through interviews, observation, documentation, and literature study. Furthermore, the researcher analyzed the data by means of data triangulation. The research conducted is about how fast employees are at work, how easy the OPERA application program is to use by employees, what are the features of the OPERA application program that are useful for employees at work, and how the productivity of the Front Office Montigo Resort Nongsa department when using the OPERA application program. Based on the results and existing discussion, it is concluded that the OPERA application program greatly affects the speed of employees when working, the OPERA application program can be easily used by most employees, the OPERA application program has many features which in use are very useful when used by employees at work, as well as the efficiency of the OPERA application program have an impact on the productivity of the Front Office Montigo Resort Nongsa department.